Aspek Hukum Penilaian atas Saham Perusahaan Startup Sebelum IPO dan Manfaatnya Bagi Investor serta Penerimaan Pajak Negara - Sita Dewi Hapsari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Valuation of shares is needed because the process of it provides important information to investors or shareholders in making investment decisions that carried out before the IPO process. Stock valuation can help investors to find out the fair value of shares and the potential profit that can be obtained from the investment. In addition, stock valuation also assists companies in determining the offering price for new shares and ensures transactions occur at a fair price for all parties involved. Stock valuation can also be used by financial institutions to determine the interest rate on loans and the amount of collateral to be provided. Therefore, the valuation of shares is an important instrument in investment and business, this is because the valuation of shares provides clear and objective information about the value of shares so as to enable investors to make decisions that can increase their profit potential. By increasing the profit earned for startup companies as well as investors, of course, it has implications for taxes as state revenue intended for the greatest prosperity of the people. Public offering regulations for Startup companies are designed to protect investors and regulate action in investment practices. However, in practice, public offering rules may still require adjustments and improvements to make them more effective in achieving their goals. As with any type of regulation, there needs to be constant review and improvement of the public offering rules to keep them effective and in line with current technological and market developments. This paper will discuss some of the latest legal aspects that need to be considered in the valuation of Startup company shares before an IPO process, to get the sight of benefits for investors and increasing tax revenues.Â